2008
DOI: 10.1134/s1990747808020116
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic transport of sodium ions in cytoplasmic and extracellular ion access channels of Na+,K+-ATPase probed by admittance measurement technique

Abstract: -Electrogenic movements of sodium ions in cytoplasmic and extracellular access channel of the Na + ,K + -ATPase have been studied by the admittance measurement technique which allows the detection of small changes of the membrane capacitance and conductance induced by phosphorylation of the ion pump. The measurements were carried out on a model system consisting of a bilayer lipid membrane, to which membrane fragments with ion pumps were adsorbed that contain the ion pumps in high density. Small changes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…This model is a generalization of the model of electrogenic transport of ions in the cytoplasmic access channel of the Na + ,K + ATPase developed earlier [13]. The model is based on the assumption that the sites of the Na + ,K + ATPase accessible from cytoplasmic side can bind not only sodium ions but also protons.…”
Section: Studies Of the Competitive Binding Of Sodium Ions And Protonsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model is a generalization of the model of electrogenic transport of ions in the cytoplasmic access channel of the Na + ,K + ATPase developed earlier [13]. The model is based on the assumption that the sites of the Na + ,K + ATPase accessible from cytoplasmic side can bind not only sodium ions but also protons.…”
Section: Studies Of the Competitive Binding Of Sodium Ions And Protonsmentioning
confidence: 99%
“…The quantitative description of this process can be considerably simplified when the fre quency of alternating voltage is low enough to assume that the ion distribution between binding sites and solution is at or close to equilibrium. As was supposed in [19], the sites are charged negatively, so that the net charge Q of the sites at equilibrium is defined by the amount of free sites which are occupied neither by ] are the sodium and proton concentra tions in the solution, K Na and K H are the sodium and proton dissociation constants, respectively, α is the fraction of the applied ac voltage, ϕ, that affects the distribution of ions in the channel (it is proportional to so called "dielectric coefficient", which is determined by the relative length of the channel [13]); β = e/kT, e is the elementary charge, k is the Boltzmann's con stant, and T, absolute temperature.…”
Section: Studies Of the Competitive Binding Of Sodium Ions And Protonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the E 2 conformation the reverse exchange is performed with the extracellular medium. In the "occluded" states, (Na 3 )E 1 -P, E 2 (K) 2 , and ATP · E 2 (K) 2 [32].…”
Section: Biophysical Methods Of Functional Analysismentioning
confidence: 99%
“…A recent study demonstrated that the access channels are impenetrable on the side where the gate is closed, i.e. the external access in E 1 and the cytoplasmic access in P-E 2 [32]. .…”
Section: The Ion-channel Model Of the Pumpmentioning
confidence: 99%